2022
DOI: 10.1039/d1na00734c
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-assisted deposition of ultra-small Au nanodots on Fe2O3/reduced graphene oxide for flexible gas sensors

Abstract: This work demonstrates introducing noble metal nanodots with suitable surface ligands in gas sensing materials is an effective way to improve their performance, and noble metal/metal oxide/rGO composites have potentials in flexible gas sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Upon exposure to NO 2 (an oxidizing gas), the BiOCl film and Bi 2 Se 3 film showed decreased and increased resistance, respectively, consistent with their p-type and n-type semiconducting properties [54][55][56][57]. However, their sensitivities are poor (e.g., 1.8% response at 1 ppm for BiOCl and 5.4% response at 1 ppm for Bi 2 Se 3 ).…”
Section: Resultsmentioning
confidence: 78%
“…Upon exposure to NO 2 (an oxidizing gas), the BiOCl film and Bi 2 Se 3 film showed decreased and increased resistance, respectively, consistent with their p-type and n-type semiconducting properties [54][55][56][57]. However, their sensitivities are poor (e.g., 1.8% response at 1 ppm for BiOCl and 5.4% response at 1 ppm for Bi 2 Se 3 ).…”
Section: Resultsmentioning
confidence: 78%
“…Wang et al 185 reported the functionalization of Au nanodots (NDs) with a size of 1.7 nanometers on the surface of α-Fe 2 O 3 /rGO for NO 2 sensing. Mercaptohexadecanoic acid (MHA) and 1-octadecanethiol (OTD) are used as ligands for different samples.…”
Section: Compounded Mos Functionalized With Au Npsmentioning
confidence: 99%
“…Fig. 13 Schematic illustration of the preparation of the flexible NO 2 sensor, with photographs of the printed Ag electrode array and flexible gas sensor coated with Au ND-ODT/a-Fe 2 O 3 /rGO 185. …”
mentioning
confidence: 99%
“…On the other hand, Wang et al [82] fabricated an interesting NO 2 gas sensor based on α-Fe 2 O 3 /rGO and Au nanodots on α-Fe 2 O 3 /rGO with 1-octadecanethiol as the surface ligand (Au ND-ODT/α-Fe 2 O 3 /rGO). Fig.…”
Section: Screen-print/epoxy Substratementioning
confidence: 99%